Auditory brainstem responses to stop consonants predict literacy. Issue 3 (March 2017) - Neef, Nicole E.; Schaadt, Gesa; Friederici, Angela D.
Highlights: Speech-evoked brainstem potentials convey the temporal precision of early speech sound encoding. Poor subcortical distinction related to poor literacy skills in 11–13-year-olds. Delta cross-phase could become a potential preclinical marker for the risk of developing dyslexia. Abstract: Objective: Precise temporal coding of speech plays a pivotal role in sound processing throughout the central auditory system, which, in turn, influences literacy acquisition. The current study tests whether an electrophysiological measure of this precision predicts literacy skills. Methods: Complex auditory brainstem responses were analysed from 62 native German-speaking children aged 11–13 years. We employed the cross-phaseogram approach to compute the quality of the electrophysiological stimulus contrast [da] and [ba]. Phase shifts were expected to vary with literacy. Results: Receiver operating curves demonstrated a feasible sensitivity and specificity of the electrophysiological measure. A multiple regression analysis resulted in a significant prediction of literacy by delta cross-phase as well as phonological awareness. A further commonality analysis separated a unique variance that was explained by the physiological measure, from a unique variance that was explained by the behavioral measure, and common effects of both. Conclusions: Despite multicollinearities between literacy, phonological awareness, and subcortical differentiation of stop consonants, a combined assessment of behavior and physiology strongly increases the ability to predict literacy skills. Significance: The strong link between the neurophysiological signature of sound encoding and literacy outcome suggests that the delta cross-phase could indicate the risk of dyslexia and thereby complement subjective psychometric measures for early diagnoses.